Bibliometric Analysis of Development Maps and Research Directions in the Field of Islamic Currency in the Scopus Database 1965-2023 - Muthoifin Muthoifin; Waston Waston; Lucísini Fersano; Ainiah Ainiah; Fahmi Dolles Marshal (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This study aims to determine the mapping of research development and research direction in the field of Islamic Currency based on research data on publications indexed in the Scopus database. The bibliometric analysis method was used in the research to explore all publications found and indexed in the Scopus database regarding Islamic Currency in the period from 1965 to 2023. The data obtained were analyzed using the help of Ms. Excel and R/R-Studio. A visual analysis of the simultaneous occurrence of keywords and document citations was conducted using VOSviewer. The author found 157 publications that have been customized based on function, subject, and predefined criteria. The results of this study show the development of research on Islamic Currency from 2010 to the present, with the most publications in 2021. Malaysia is the most contributing country for publications in this field, with Universiti Kebangsaan Malaysia as the highest contributing affiliate. Yaacob, S.E is the author with the most publications in the theme of Islamic Currency. The bibliometric analysis conducted was limited to Scopus data only. Other national or international databases were not taken into account in this study. This study presents a brief overview of the literature that can be accessed by researchers in the field of Islamic Currency and provides recommendations for future research.